LQR controller for active car suspension - Md. Sam, Yahaya; Ab. Ghani, Mohd. Ruddin; Ahmad, Nasarudin (2000)

(untitled)
The suspension system is classified as a passive, semi-active, and active suspension, according to its ability to add or extract energy. An automotive active suspension control has been one of the favourite subjects in the automotive research area. The advantages of an automotive active suspension system have been promised for many years. The objectives of the control scheme are to improve the ride quality and handling performance within a given suspension stroke limitation. The ride quality is measured by the vertical acceleration of the vehicle body called the sprung mass. The handling performance is determined by the tyre deflection, which is the difference of position between the wheel and the road surface input. The paper analyses the aspects of passive and active suspensions and focuses on the ride quality improvement. The LQR control scheme is selected to control an actuator in an active suspension. The result shows that the ride quality can be improved using an active suspension